2009
DOI: 10.1177/0192623309335630
|View full text |Cite
|
Sign up to set email alerts
|

γ-Tocopherol Attenuates Ozone-induced Exacerbation of Allergic Rhinosinusitis in Rats

Abstract: Compared to healthy subjects, individuals with allergic airway disease (e.g., asthma, allergic rhinitis) have enhanced inflammatory responses to inhaled ozone. We created a rodent model of ozone-enhanced allergic nasal responses in Brown Norway rats to test the therapeutic effects of the dietary supplement g-tocopherol (γT). Ovalbumin (OVA)-sensitized rats were intranasally challenged with 0% or 0.5% OVA (in saline) on Days 1 and 2, and then exposed to 0 or 1 ppm ozone (eight hours/day) on Days 4 and 5. Rats w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 49 publications
4
22
0
Order By: Relevance
“…γ-Tocopherol scavenging of RNS may be beneficial for inflammation with increases in RNS such as neutrophilic inflammation that is induced by ozone or endotoxin in mice 23 . Consistent with this, reports indicate that supplementation with a mixture of tocopherols enriched for γ-tocopherol blocks acute endotoxin-stimulated or ozone-stimulated neutrophil inflammation in the rat and human lung 2426 . In another study, γ-tocopherol supplementation reduced antigen induction of rat lung inflammation in which there was several fold more neutrophils than eosinophils 27 .…”
Section: Vitamin Esupporting
confidence: 65%
“…γ-Tocopherol scavenging of RNS may be beneficial for inflammation with increases in RNS such as neutrophilic inflammation that is induced by ozone or endotoxin in mice 23 . Consistent with this, reports indicate that supplementation with a mixture of tocopherols enriched for γ-tocopherol blocks acute endotoxin-stimulated or ozone-stimulated neutrophil inflammation in the rat and human lung 2426 . In another study, γ-tocopherol supplementation reduced antigen induction of rat lung inflammation in which there was several fold more neutrophils than eosinophils 27 .…”
Section: Vitamin Esupporting
confidence: 65%
“…g-Tocopherol scavenging of reactive nitrogen species may be beneficial for inflammation with increases in reactive nitrogen species, such as neutrophilic inflammation that is induced by ozone in mice (22). Consistent with this, reports indicate that supplementation with a mixture of tocopherols that are enriched for g-tocopherol blocks acute endotoxin-stimulated or ozone-stimulated neutrophil inflammation in the rat and human lung (23)(24)(25). In another study, g-tocopherol supplementation reduced antigen induction of rat lung inflammation that was primarily neutrophils (26).…”
mentioning
confidence: 73%
“…Studies have shown anti-inflammatory potential of γ-tocopherol and its metabolites probably via inhibition of cyclooxygenase-catalyzed synthesis of prostaglandin E 2 (PGE 2 ) (Reiter, Jiang, & Christen, 2007;Wagner, Jiang, Harkema, Illek, Patel, Ames et al, 2007;Jiang et al, 2008;Jiang, Moreland, Ames, & Yin, 2009;Wagner, Harkema, Jiang, Illek, Ames and Peden, 2009). The content of γ-tocopherol in raspberry seed oil is several times higher than the contents reported in commonly used vegetable oils (10-60 mg/100 g) (Gunstone & Harwood, 2007).…”
Section: Tocopherols and Tocotrienolsmentioning
confidence: 99%